2018
DOI: 10.3168/jds.2018-14824
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-specific production losses in bovine mastitis

Abstract: Reduction in long-term milk yields represents a notable share of the economic losses caused by bovine mastitis. Efficient, economic, and safe measures to prevent these losses require knowledge of the causal agent of the disease. The aim of this study was to investigate pathogen-specific impacts of mastitis on milk production of dairy cows. The materials consisted of milk and health recording data and microbiological diagnoses of mastitic quarter milk samples of 20,234 Finnish dairy cows during 2010, 2011, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 60 publications
5
138
2
12
Order By: Relevance
“…The role of minor pathogens in causing IMI and the subsequent effect on the SCC and production have been extensively debated in the literature (e.g., Harmon, 1994;Pyörälä and Taponen, 2009;Schukken et al, 2009;De Vliegher et al, 2012), and it is unclear when minor pathogens constitute a problem due to the highly variable pathogenicity within this group. A recent study showed that minor pathogens can impair the performance of dairy cows, for example, causing production loss (Heikkilä et al, 2018). Nonetheless, because the presence of minor pathogens may not always be associated with increased SCC (e.g., Figure 2), DSCC might be a useful addition for indicating problems with minor pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The role of minor pathogens in causing IMI and the subsequent effect on the SCC and production have been extensively debated in the literature (e.g., Harmon, 1994;Pyörälä and Taponen, 2009;Schukken et al, 2009;De Vliegher et al, 2012), and it is unclear when minor pathogens constitute a problem due to the highly variable pathogenicity within this group. A recent study showed that minor pathogens can impair the performance of dairy cows, for example, causing production loss (Heikkilä et al, 2018). Nonetheless, because the presence of minor pathogens may not always be associated with increased SCC (e.g., Figure 2), DSCC might be a useful addition for indicating problems with minor pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…As a group, the NAS are the most prevalent (ranging from 9.1 to 16.6% of milk samples) causative agents of IMI in dairy cows in many regions (Wilson et al, 1997;Pitkälä et al, 2004;Tenhagen et al, 2006), and are typically more isolated from subclinical than from clinical cases of mastitis (Persson Waller et al, 2011;Heikkilä et al, 2018). The relevance of NAS IMI with regard to the effect on milk production in affected The effect of intramammary infection in early lactation with non-aureus staphylococci in general and Staphylococcus chromogenes specifically on quarter milk somatic cell count and quarter milk yield D. Valckenier, 1 S. Piepers, 1 A.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the contradiction can be attributed to differences in the length of the follow-up period, breed, parity, diagnostic methods, and definition of IMI status among the studies. More recent studies, considering only heifers (Valckenier et al, 2019) or cows of all parities (Tomazi et al, 2015;Heikkilä et al, 2018), still consider NAS (as a group) to be minor pathogens, only slightly elevating the quarter milk SCC (qSCC) in case of subclinical mastitis, and with little or no effect on the quarter milk yield (qMY).…”
Section: Introductionmentioning
confidence: 99%
“…The need to know the health status of dairy herds is essential to increase herd efficiency and sustainability (Pulina et al 2017). Among the diseases affecting dairy cows, mastitis is still the most important one significantly affecting the profits of dairy farmers (Summer et al 2015;Goncalves et al 2018;Heikkil€ a et al 2018). Furthermore, this aspect is important when protocols based on a prudent use of antibiotics should be applied on such as selective dry cow therapy (Trevisi et al 2014;Zecconi, Sesana, et al 2018).…”
Section: Introductionmentioning
confidence: 99%